(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Central Asia is at the intersection of interests of many countries as a promising region in terms of ensuring domestic and European energy independence. The outbreak of armed conflicts, religious conflicts, conflicts over social issues and general inequality continue to be a complex factor in international relations. Many of the region’s problems are closely interconnected, and each of them together threatens the stability of the region. Such problems include external threats, religious extremism and terrorism, drug trafficking, border problems, water shortages, social problems, unemployment, migration and a number of other factors. The energy crisis and diversification of energy resources are also relevant. In the context of internal difficulties, conflicts and tensions over the demand for water resources, terrorism and extremism, drug trafficking, border disputes, the national security of the Central Asian states is at risk, since its supply system is under pressure from all sides. Studying the topic of international cooperation of Central Asian countries on regional security issues is an urgent and pressing need.